EFFECT ANALYSIS OF CAR, BOPO, LDR, LEVERAGE, NPL AND COMPANY SIZE ON FINANCIAL PERFORMANCE WITH INTELLECTUAL CAPITAL AS A VARIABLE MODERATING IN BANKING COMPANIES LISTED ON STOCK EXCHANGE INDONESIA - Rizky Surya Andhayani Nasution; Sri Liniarti (Jurnal Mantik, 2022)
Research objectives this is analyze CAR influence , BOPO, LDR, Leverage , NPL and size company t against k performance k finance p exists p company banking on the Indonesian Stock Exchange by simultaneous and partial . Study it also analyzes influence of Intellectual Capital in moderate connection Among CAR, BOPO, LDR, Leverage , NPL and size company with k performance k finance p exists p company banking on the Indonesian Stock Exchange. Population in study this is whole company banking listed on the Indonesia Stock Exchange for 20102014 period , namely as many as 41 banks. retrieval technique sample used _ in study this is method purposive sampling, so that obtained 26 banks that became sample study with total observation as many as 130 data. The data analysis method used in study this is an analytical model multiple linear regression and residual test . Data used is secondary data in the form of report finance banks listed on the IDX for period 2010-2014. Test results hypothesis show that by simultaneous CAR, BOPO, LDR, Leverage , NPL and size company influential significant to performance finance banking (ROA) will but by Partial NPL and influential CAR no significant to performance finance (ROA). Study it also shows there is influence intellectual capital moderation however result no significant.